Pembuatan Aplikasi Web Pengelolaan Labor Komputer Di Program Studi Teknik Informatika Politeknik Kampar - Fenty Oktorina; Safni Marwa (Jurnal Sains dan Ilmu Terapan, 2019)
The unavailability of an information system that functions to manage computer labor in the Kampar Polytechnic Informatics Engineering study program has resulted in the implementation of work procedures being carried out manually and of course it will take quite a long time. This allows errors to occur in the implementation of computer labor management. A web-based system for computer labor management will be a solution to the constraints faced by the Informatics Engineering study program related to manual lab management. This web application is expected to be able to record information on events in the lab, such as damage, equipment presence, tool transfer to loss. This information will become inventory data for tools and goods which will later be reported to the leadership